Group B Streptococcal Maternal Colonization and Neonatal Disease: Molecular Mechanisms and Preventative Approaches - Patras, Kathryn A.; Nizet, Victor (Frontiers in Pediatrics, 2018)
Group B Streptococcus (GBS) colonizes the gastrointestinal and vaginal epithelium of a significant percentage of healthy women, with potential for ascending intrauterine infection or transmission during parturition, creating a risk of serious disease in the vulnerable newborn. This review highlights new insights on the bacterial virulence determinants, host immune responses, and microbiome interactions that underpin GBS vaginal colonization, the proximal step in newborn infectious disease pathogenesis. From the pathogen perspective, the function GBS adhesins and biofilms, β hemolysin/cytolysin toxin, immune resistance factors, sialic acid mimicry and two-component transcriptional regulatory systems are reviewed. From the host standpoint, pathogen recognition, cytokine responses and the vaginal mucosal and placental immunity to the pathogen are detailed. Finally, the rationale, efficacy and potential unintended consequences of current universal recommended intrapartum antibiotic prophylaxis are considered, with updates on new developments toward a GBS vaccine or alternative approaches to reducing vaginal colonization.